Unraveling the Molecular Mechanisms of Mosquito Salivary Proteins: New Frontiers in Disease Transmission and Control - Jiayin Guo; Xiaoe He; Jianli Tao; Hui Sun; Jing Yang (Biomolecules)
Mosquito-borne diseases are a group of illnesses caused by pathogens transmitted by mosquitoes, and they are globally prevalent, particularly in tropical and subtropical regions. Pathogen transmission occurs during mosquito blood feeding, a process in which mosquito saliva plays a crucial role. Mosquito saliva contains a variety of biologically active proteins that facilitate blood feeding by preventing blood clotting, promoting vasodilation, and modulating the host’s immune and inflammatory responses. These effects create an environment conducive to pathogen invasion and dissemination. Specific mosquito salivary proteins (MSPs) can promote pathogen transmission through mechanisms that either regulate hosts’ anti-infective immune responses or directly enhance pathogens’ activity. Strategies targeting these MSPs have emerged as an innovative and promising approach for the control of mosquito-borne diseases. Meanwhile, the diversity of these proteins and their complex interactions with the host immune system necessitate further research to develop safer and more effective interventions. This review examines the functional diversity of MSPs and their roles in disease transmission, discusses the advantages and challenges of strategies targeting these proteins, and explores potential future directions for research in this area.